Infantile hepatic hemangioma and hepatic mesenchymal hamartoma in an infant associated with placental mesenchymal dysplasia: a case report - Shunsuke Fujii; Kyoko Mochizuki; Hidehito Usui; Norihiko Kitagawa; Sayoko Umemoto; Mio Tanaka; Yukichi Tanaka; Masako Otani; Kumiko Nozawa; Kenji Kurosawa; Masayo Kagami; Masato Shinkai (Surgical Case Reports, 2022)
Abstract Background Although infantile hepatic hemangioma and hepatic mesenchymal hamartoma are relatively common in benign pediatric liver tumors, coexistence of the two tumors is rare. Placental mesenchymal dysplasia is also a rare disorder. We report the case of a baby girl born after a pregnancy complicated by placental mesenchymal dysplasia, who developed both infantile hepatic hemangioma and hepatic mesenchymal hamartoma. Case presentation The patient was born at 32 weeks and 5 days of gestation for impending placental abruption, weighing 1450 g. Liver tumors, composed of both hypervascular solid and large cystic lesions, were detected after birth and markedly increased to create abdominal distention within 9 months. Diagnostic imaging suspected the coexistence of infantile hepatic hemangioma and cystic hepatic mesenchymal hamartoma. Following propranolol therapy for infantile hepatic hemangioma and needle puncture of a large cyst, the cystic lesions and adjacent hypervascular lesions were partially resected via laparotomy. Pathological findings confirmed the coexistence of hepatic mesenchymal hamartoma and infantile hepatic hemangioma, which had no association with androgenetic/biparental mosaicism. The postoperative course was uneventful, and the tumor had not regrown after 3 years. Conclusions Although the coexistence of infantile hepatic hemangioma and hepatic mesenchymal hamartoma associated with placental mesenchymal dysplasia is extremely rare, the pathological and pathogenetic similarities between these disorders suggest that they could have derived from similar embryologic origins rather than being a mere coincidence. Further follow-up is required, with careful attention to the potential for malignant hepatic mesenchymal hamartoma transformation.